Effects of Rolipram and Zaprinast on Learning and Memory in the Morris Water Maze and Radial Arm Maze Tests in Naive Mice - Akar, F.; Mutlu, O.; Celikyurt, I. K.; Ulak, G.; Erden, F.; Bektas, E.; Tanyeri, P. (Drug Research, 2015)
Inhibition of phosphodiesterase 5 (PDE) improved recognition memory and counteracted spatial learning impairment induced by nitric oxide synthase (NOS) inhibition in recent studies. Aim of this study was to investigate effects of rolipram, a PDE4 inhibitor and zaprinast, a PDE5 inhibitor, on learning and memory in Morris water maze (MWM) and radial arm maze (RAM) tests in naive mice. Male Balb-c mice were treated subchronically with zaprinast (3 and 10 mg/kg) and rolipram (0.05 and 0.1 mg/kg) for 6 days in the MWM test and acutely before the retention trial of radial arm maze test. Rolipram (0.05 and 0.1 mg/kg) significantly decreased escape latency between 2nd and 5th sessions, while zaprinast (10 mg/kg) significantly decreased escape latency only in 2nd session. Rolipram (0.05 and 0.1 mg/kg) and zaprinast (10 mg/kg) significantly increased time spent in escape platform’s quadrant in probe trial of MWM test; only rolipram decreased mean distance to platform, while zaprinast had no effect on mean distance to platform. Zaprinast (3 and 10 mg/kg) significantly decreased number of errors compared to control group, while rolipram (0.05 and 0.1 mg/kg) had no effect on number of errors in retention trial of RAM test. Rolipram (0.05 and 0.1 mg/kg) and zaprinast (10 mg/kg) significantly decreased time spent to complete retention trial (latency) compared to control group. Our study revealed that both zaprinast and rolipram enhanced spatial memory in MWM, while zaprinast seems to have more memory enhancing effects compared to rolipram in radial arm maze test.
Keywords: zaprinast; rolipram; memory; mice